Exploring the age of taekwondo athletes in the Olympic Games: an analysis from Sydney 2000 to Rio 2016 - Apollaro, G.; Ruscello, B. (The Journal of Sports Medicine and Physical Fitness, 2022)
BACKGROUND: The aim of this study was to quantify the age at which taekwondo athletes competed in the Olympic Games and to provide initial insights into weight category changes over time. METHODS: For the first analysis, the study included all 611 taekwondo athletes who competed in the Olympics between 2000 and 2016; for each sex, a three-way ANOVA (edition of Olympic Games, competitive achievement, weight category) was performed to detect differences in the age of athletes. For the second analysis, we considered all 109 taekwondo athletes who took part in more than one edition of the Olympics between 2000 and 2016; chi-squared goodness of fit tests were performed to study the number of participations and changes in weight category of these athletes. RESULTS: Female athletes, with a mean age of 23.8±4.1 years, are significantly younger (P=0.001) than their male counterparts, with a mean age of 25.1±3.9 years. In weight category, lighter athletes being younger than heavier ones in both females (22.7±3.7 vs. 24.5±4.2 years, P=0.04) and males (23.6±3.8 vs. 26.7±3.8 years, P=0.001; 24.2±3.5 vs. 26.7±3.8 years, P=0.001). When an athlete reaches Olympic competition several times, he/she generally competes in the same weight category (P=0.001) and takes part in two consecutive editions (P=0.001). Heavier athletes have greater longevity at Olympic level than lighter athletes (P=0.002). CONCLUSIONS: The current data provides important information for national federations engaged in the selection of athletes for Olympic competitions.